Study Habits and Examination Anxiety as Correlates of Academic Performance Among Secondary School Students in Kwara State, Nigeria - Ilori, Oyedotun Dolapo; Okesina, Falilat A.; Akerele, Patrick O.; Michael, Ifeoluwa Blessing (citeus, 2025)
Examination anxiety and study habits seem to be a significant factor of academic performance. This study examined study habits and examination anxiety as correlates of academic performance among secondary school students in Kwara State, Nigeria. This study adopted a descriptive survey of correlational type. The population for the study consists of 235, 652 secondary school students, and the sample consists of 400 secondary school students. Two research questions were answered using frequency count, percentage and mean rank order while the three hypotheses formulated were tested using inferential statistics of Pearson’s Product Moment Correlation statistics (PPMC) and multiple regression analysis at 0.05 level of significance. The findings of the study revealed that there is a significant relationship among study habits, examination anxiety and the academic performance of students. Findings also revealed that there is a significant relationship between study habits and the academic performance. The result of the findings of this study further revealed that there is a significant relationship between examination anxiety and the academic performance. Based on the findings, it was recommended that the government of Nigeria should provide adequate resources, such as 21st century learning classrooms, updated libraries and e-libraries and computers to improve the teaching and learning processes for secondary school students.